تبني تقنية التحفيز الضوئي في معالجة النفايات الطبية:نحو تحقيق الاستدامة البيئية- تحليل للعوائد المتوقعة وفقا لتطبيقات ميدانية- - ينون, أمال (جامعة الوادي - University of Eloued, 2022)
غذت تقنية التحفيز الضوئي من التقنيات الواعدة في مجال معالجة النفايات الطبية، والتخلص من مضارها السلبية والخطيرة على النظم الصحية والبيئية. وقد لاقت هذه التقنية تسويقا مهما في مجال معالجة المياه، وهذا ما صوب الرؤية لإمكانية اعتمادها في المجال الطبي لما يميزها عن باقي التقنيات ولما تطرحه من خيار إستراتيجي يتماشى مع أهداف التنمية المستدامة. وفي هذا المنحنى، تهدف هذه الدراسة للوقوف على آلية عمل هذه التقنية في مجال معالجة النفايات الطبية. وتوصلت الدراسة، إلى أن تقنية التحفيز الضوئي تعد بارقة أمل للحقل الطبي في تحقيق أداء متميز للمنظمات الإستشفائية، وأنها التقنية التي يتوقع أن تسهم في بناء قطاع صحي وبيئي مستدام محققا لأهداف جودة الحياة البشرية. field of medical waste treatment and the disposal of its negative and dangerous effects on environmental and health systems. This technology has received significant marketing in water treatment field; this is to be adopted in the medical field; because of what distinguishes it from other technologies, and because it offers a strategic choice consistent with the sustainable development goals. this regard, this study aims to determine the work mechanism of this technology in the area of medical waste treatment, and its importance for environmental sustainability. The study concluded that the photocatalytic technology is a glimmer of hope for the medical field in achieving an outstanding performance for hospital organizations, and that it is the technology that is expected to contribute in building a sustainable health and environmental sector to achieve the goals of the quality of human human life.
Adoption of Photocatalytic Technology in Medical Waste Treatment: Towards Achieving The Environmental Sustainability-Analysis of expected yields according to field applications
مقال
Keywords: تحفيز ضوئي ; نفايات طبية ; تنمية مستدامة ; استدامة بيئية ;; Photocatalytic Technology ; Medical Waste ; Sustainable Development